Water vapor concentration measurements using TDALS with wavelength modulation spectroscopy at varying pressures. Issue 2 (20th March 2017) - Wei, Wei; Chang, Jun; Huang, Qingjie; Wang, Qiang; Liu, Yuanyuan; Qin, Zengguang
Abstract : Purpose: As measurement results of optical gas sensors are constantly affected by the pressure of a target gas, approaches must be taken to modify the results. The purpose of this paper is to compare the traditional measurement method with the new measurement system. At the same time, measurement results of the two systems under different pressures are presented for comparison of the detection performance. Design/methodology/approach: A theoretical model of line shape function and its impact on the measured results is presented, which is based on direct absorption and wavelength modulation spectroscopy (WMS) for gas concentration detection under different pressures. Methods of linear fitting and result modification have been illustrated and compared. A new testing system with the result modification method used for water vapor concentration detection under different pressures between 1 and 7 atm is applied. With an additional pressure sensor placed in the gas cell and calibration performed, relationships between the amplitude of the second harmonic and concentration of the target gas under different pressures can be obtained. Findings: Amplitude detection can be used for concentration detection regardless of the change in pressure for the method of direct absorption. Although, WMS with second harmonic detection is not enough. Two methods are presented and compared with WMS under different pressures. Moreover, the result modification method shows better performance as computation is significantly reduced. Originality/value: The comparison between linear fitting and the result modification method with WMS under different pressures is firstly presented. At the same time, a new testing system with better performance for water vapor concentration detection under different pressures is presented as well.